2010
DOI: 10.1002/jor.21192
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical T2* MR quantification of ankle arthrosis in pes cavovarus

Abstract: Pes cavovarus affects the ankle biomechanics and may lead to ankle arthrosis. Quantitative T2 STAR (T2*) magnetic resonance (MR) mapping allows high resolution of thin cartilage layers and quantitative grading of cartilage degeneration. Detection of ankle arthrosis using T2* mapping in cavovarus feet was evaluated. Eleven cavovarus patients with symptomatic ankle arthrosis (13 feet, mean age 55.6 years, group 1), 10 cavovarus patients with no or asymptomatic, mild ankle arthrosis (12 feet, mean age 41.8 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…Many of these techniques utilize the physics of water molecule relaxation within a magnetic field to produce images, which highlight the presence of proteoglycans (T1rho), hydration level (T2), and structure of the macromolecule matrix along with hydration level (T2*). Quantitative T2* (T2 star) mapping is an emerging technique with the added benefit of a short acquisition time, high signal-to-noise ratio, and three-dimensionality over traditional T2 mapping 11,17,18 . T2* has been shown to probe biochemical properties of the tissues and has been beneficial in cartilage 10,11,1724 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these techniques utilize the physics of water molecule relaxation within a magnetic field to produce images, which highlight the presence of proteoglycans (T1rho), hydration level (T2), and structure of the macromolecule matrix along with hydration level (T2*). Quantitative T2* (T2 star) mapping is an emerging technique with the added benefit of a short acquisition time, high signal-to-noise ratio, and three-dimensionality over traditional T2 mapping 11,17,18 . T2* has been shown to probe biochemical properties of the tissues and has been beneficial in cartilage 10,11,1724 .…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative T2* (T2 star) mapping is an emerging technique with the added benefit of a short acquisition time, high signal-to-noise ratio, and three-dimensionality over traditional T2 mapping 11,17,18 . T2* has been shown to probe biochemical properties of the tissues and has been beneficial in cartilage 10,11,1724 . Specifically, T2* relaxation times provide information about spatial macromolecule architecture in conjunction with water molecule mobility 11,18 .…”
Section: Introductionmentioning
confidence: 99%
“…T2* has also proven to be a reliable and valid method in biochemical cartilage imaging [14]. Few available studies imply a close relationship to T2; nevertheless, T2* seems to be more dependent on micro-structural tissue changes and has shorter imaging times providing the same spatial resolution; therefore T2* appears to be an adequate diagnostic method that can be implemented into a clinical MR protocol [15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it results in the relative increase of water content in the articular cartilage substrate [12, 48] and thus the T2* relaxation time will be extended. Several studies have shown that GRE T2*WI can be used to evaluate changes in the early articular cartilage degeneration of biological tissue structure with no obvious morphological changes [12, 49]. This has important clinical value for early articular cartilage degeneration.…”
Section: Clinical Applicationmentioning
confidence: 99%